STRATEGI PENGELOLAAN PASAR IKAN MODERN DI PELABUHAN PERIKANAN SAMUDERA NIZAM ZACHMAN JAKARTA - Iin Solihin; Ni Ketut Leni Meilani; Retno Muninggar (Bogor Agricultural University, 2020)
Modern Fish Market (MFM) is the result of relocation from the Fish Marketing Center (FMC) located at the Nizam Zachman Ocean Fisheries Port in Jakarta (NZOFPJ). The relocation of the market has caused traders to protest against the manager. One of their actions is to go on a fish payment strike, which affects the stability MFM cash flow. Accordingly, the management needs to investigate the financial condition of MFM to determine future actions for the market sustainability. However, no study has been conducted regarding the financial condition of MFM. This study aims to determine the comparison of MFM and FMC revenue and strategies to improve the existing situation. A case study was conducted in the Nizam Zachman Fishing Port in Jakarta. Financial data of MFM and FMC including problems encountered by MFM were collected from the business division of Perum Perindo Jakarta, MFM management team and MFM traders. Revenue analysis, SWOT analysis as well as Quantitative Strategic Planning Matrix were perfomed in this study. The results showed that revenue generated by the MFM was IDR 1,474,085,972.00, which is lower than the FMC revenue (IDR 2,360,855,000.00). In order to improve MFM financial situation, nine strategies have been formulated and primarily it has been focused on the development of small and medium enterprises. Keywords: revenue, management, modern fish market, NZOFPJ, strategy.